RESENSI: NGASIRAH, PEREMPUAN TANGGUH DI BALIK R.A. KARTINI - Widowati Widowati (CARAKA, 2017)
The Book Kartini Kisah yang Tersembunyi  of Aguk Irawan opens another color in the life of a national hero, R.A. Kartini. It should be realized that the writing of one's biography is never singular, as a work of fiction. Precisely with the diversity of biography writing will enrich the reader in capturing, understanding, and interpreting the biography or history.